2022
DOI: 10.3390/toxics10050201
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Impact of End-of-Life-Tire (ELT)-Derived Rubbers: Acute and Chronic Effects at Organism and Population Levels

Abstract: Considering the large amount of tires that reach the end of life every year, the aim of this study was the evaluation of both acute and chronic effects of end-of-life-tire (ELT)-derived rubber granules (ELT-dg) and powder (ELT-dp) on a freshwater trophic chain represented by the green alga Pseudokirchneriella subcapitata, the crustacean Daphnia magna and the teleost Danio rerio (zebrafish). Adverse effects were evaluated at the organism and population levels through the classical ecotoxicological tests. Acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The polymer was also listed by Brown (2022) as a hazardous agent from plastic processing. Although Magni et al (2022) found that they do not hold a great threat towards freshwater organisms and the FESEM images of aged foam and the corresponding EDX spectra of aged foam recovered from the estuarine environment of Penang. Tan and Mohd Zanuri 10.3389/fmars.2023.1148804 Frontiers in Marine Science frontiersin.org environment, the authors suggested more studies to be conducted due to its gradual emergence in the aquatic environment.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 87%
“…The polymer was also listed by Brown (2022) as a hazardous agent from plastic processing. Although Magni et al (2022) found that they do not hold a great threat towards freshwater organisms and the FESEM images of aged foam and the corresponding EDX spectra of aged foam recovered from the estuarine environment of Penang. Tan and Mohd Zanuri 10.3389/fmars.2023.1148804 Frontiers in Marine Science frontiersin.org environment, the authors suggested more studies to be conducted due to its gradual emergence in the aquatic environment.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 87%
“…The Toxicity Characteristic Leaching Procedure (TCLP) was used to determine concentrations of leached tire components. Magni S [74] conducted an in-depth analysis of tire components and secondary contamination chemicals and reported 31 PAHs, 31 metals, 8 benzothiazoles, 6 phenols, 15 phthalates, 9 hydrocarbon oils, 10 amine-nitrosamines, 9 halogenated organic aromatic compounds, 35 others, polymer contents, and ashes. However, under environmental conditions, the composition of the leachates will be quite different due to variable solubility in water and other chemical properties.…”
Section: Leaching Test Methodsmentioning
confidence: 99%
“…As a recycled organic component, the use of rubber pellets in Portland cement concrete can effectively address environmental concerns and is already an opportunity to reduce the consumption of environmentally friendly materials while reducing landfill. Several researchers referred to the decrease of the mechanical properties of rubberized concrete, and some researchers reported the enhancement of the properties of the rubber crumbs particles using pretreatment of rubber crumbs surface to be compatible with cement matrix, but less information was provided regarding rubber crumbs hazardous impact to the environment and how to mitigate it [11]; [7]. Chemical elements which consist in ELT it is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%